Analisis Pengaruh Kualitas Layanan dan Kualitas Informasi Terhadap Kepuasan Pengguna pada Platform Pembelajaran Daring - Rafliansyah Fajar Ramadhan; Rizki Sani Nurahmat; Rayyan Fadli (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
This study aims to analyze the effect of service quality and information quality on user satisfaction in online learning platforms. The rapid development of information technology has encouraged higher education institutions to adopt online learning systems to support teaching and learning activities. This research uses a quantitative approach with a survey method. Data were collected from 150 students who actively use online learning platforms. The data analysis technique applied was multiple linear regression analysis. The results indicate that service quality and information quality have a positive and significant effect on user satisfaction. These findings suggest that improving service responsiveness, system support, and the accuracy and relevance of information can enhance user satisfaction with online learning platforms.